Exploiting Substrate Cues for Co-Culturing Cells in a Micropattern - Joshi, Akshay (Langmuir : the ACS journal of surfaces and colloids, 2021)
Spatial distribution of cells and their interactions between neighboring cells in native microenvironments are of fundamental importance in determining cell fate decisions such as migration, growth, and differentiation. Controlling the spatial distribution of different cell types in defined geometries can replicate these native environments, which can be a useful model for several studies. While spatiotemporal control over multiple cell arrangements is required to achieve the complex tissue architecture, unfortunately, conventional cell patterning techniques usually allow only single patterning with a single cell type. In the present study, we introduce a simple lithographic method to pattern multiple cell types in a spatially controlled manner by utilizing the biophysical cues present at the corners of the patterned geometry. By fabricating micropatterns of different shapes, we demonstrate how the cell can be constrained to pattern along the corners of patterned geometries owing to the presence of topographical cues, leaving empty voids in the center that can be further utilized for patterning a second cell type. We also demonstrate that the cell alignment along the pattern is a dynamic process and the cells migrate from a more uniform cell-adhesive region toward the topographical cues. The cytoskeleton arrangement was geometry-dependent, which was confirmed through a series of in vitro evaluations, such as scanning electron microscopy and fluorescence microscopy. These findings have not only helped us in exploring the importance of these cues in guiding the cell fate but have also allowed us to develop a technique, which self-patterns the cells without any expensive exogenous cues and can be used as a model protocol to eventually organize cells into a specific pattern with micron-scale precision in vitro